The Effect of Quarter Turn from Prone on Oxygen Saturation among Premature Babies with Respiratory Distress Syndrome - Lestari, Puji; Susmarini, Dian; Awaludin, Sidik (Jurusan Keperawatan FIKES UNSOED, 2018)
The rate of death and illnesses on premature babies is mostly respiratory distress syndrome (RDS). Desaturated-period frequently occurs on premature babies with RDS. One intervention to prevent it is a quarter turn from prone position. The research design was pre-experimental study with one group pre- and post-test design. This study involved 20 respondents that were selected with consecutive sampling technique. The setting of the research was in Perinatology ward at Prof. Dr. Margono Soekarjo. The oxygen saturation was examined before and after 2 hours of intervention. Data was then analyzed with Wilcoxon test. The results showed that median value of SpO2 before quarter turn from prone position was 94%, and its value after two hours of intervention was 96.5%. It was found that there was a significant effect in giving quarter turn from prone position to oxygen saturation on premature babies with RDS. Quarter turn from prone position was able to increase oxygen saturation on premature babies with RDS and is possible to be implemented in perinatology room.